2020
DOI: 10.5812/jcrps.96303
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Cognitive and Physical Components in Volleyball Injuries Prediction

Abstract: Background: Researchers have always sought to investigate the factors affecting sports injuries in order to identify ways of preventing and controlling such factors. These studies have more emphasis on physical aspects, while the cognitive and psychological components may also be effective. Objectives: The present study was conducted to answer the question whether or not injury can be predicted in volleyball athletes through physical and cognitive components. Methods: For this purpose, 50 volleyball players wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In this environment, achieving optimal performance becomes crucial for team success. Previous research had shown that psychological and mental factors play a significant role in reaching peak performance in volleyball athletes (Hesami et al, 2020;Machado et al, 2018;Mendes et al, 2017). Therefore, developing effective methods to optimise the psychological and mental aspects of volleyball athletes can provide significant competitive advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In this environment, achieving optimal performance becomes crucial for team success. Previous research had shown that psychological and mental factors play a significant role in reaching peak performance in volleyball athletes (Hesami et al, 2020;Machado et al, 2018;Mendes et al, 2017). Therefore, developing effective methods to optimise the psychological and mental aspects of volleyball athletes can provide significant competitive advantages.…”
Section: Introductionmentioning
confidence: 99%